Effectiveness of Informational Pamphlet on Self-Care Practices Within Hypertensive Patients - Malik, Priyanka Mohan; Chendake, Mahesh B; Mohite, Namarta C; Shinde, Mahadeo B (International Journal of Psychosocial Rehabilitation, 2020)
Introduction- Hypertension is said to be the most common health problem all over the world. Worldwide due to hypertension approximately 25% of the adult population is affecting. The prevalence of hypertension in India is 29.8%.Objective:The study investigated the effectiveness of Informational pamphlets on Self Care Practices among Hypertensive Patients. Methods: one group pre-test post-test design was used.60 hypertensive patients were selected by the purposive sampling technique. Data was collected by using a structured questionnaire.Results: Maximum number 25(41.66%) of samples belong to the group of age of 46-60 years,The maximum number of samples 25(41.66%) belongs to secondary education,18(30%) samples belong to graduate education.The majority number of samples 49 (81.66%) belongs to Hindu religion,The majority of Samples 40(66.66%) belong to the rural area, The maximum number of Samples 39(65%) belongs to their income of less than Rs.10000. Majority of Samples 22(36.66%) belongs to housewife,.A maximum number of samples 60(100%) had got the information regarding their disease from the book. the pre-test most of the samples were having average knowledge (70%) regarding self-care practices regarding hypertension and in the post-test majority (99.66%) were having good knowledge. The pretest mean was 12.08 and the post-test mean was 18.78 and the calculated t value was 6.70 found significant at the level of p<0.0001.Conclusion:Study concluded that information pamphlet was found effective to improve the knowledge related self-care practices among hypertensive patients.